2006
DOI: 10.1117/12.658711
|View full text |Cite
|
Sign up to set email alerts
|

Wireless threshold sensors for detecting corrosion in reinforced concrete structures

Abstract: The long-term reliability of a threshold corrosion sensor is demonstrated using data collected during two series of exposure tests. The sensors were embedded in concrete and interrogated in a wireless manner using inductive coupling. The frequency signature of the sensor changes after a steel sensing wire corrodes, providing a convenient and noninvasive technique for determining when a threshold amount of corrosion has occurred in a reinforced concrete structure.In the first series of exposure tests, the senso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…The sensors in Slab 1 were fabricated with 26-gauge (0.40-mm diameter) steel wire and the sensors in Slab 2 were fabricated with 21-gauge (0.72-mm diameter) steel wire. Tests of sections of steel wires submerged in saltwater had indicated that smaller-diameter wires corroded in a shorter period of time than did larger-diameter wires (1, 2), and these slabs were designed to determine if different corrosion thresholds could be detected for embedded sensors by varying the size of the steel sensing wire (2). There was no electrical connection between the sensing wires and the top layer of reinforcement in Slabs 1 and 2.…”
Section: Long-term Exposure Testsmentioning
confidence: 99%
“…The sensors in Slab 1 were fabricated with 26-gauge (0.40-mm diameter) steel wire and the sensors in Slab 2 were fabricated with 21-gauge (0.72-mm diameter) steel wire. Tests of sections of steel wires submerged in saltwater had indicated that smaller-diameter wires corroded in a shorter period of time than did larger-diameter wires (1, 2), and these slabs were designed to determine if different corrosion thresholds could be detected for embedded sensors by varying the size of the steel sensing wire (2). There was no electrical connection between the sensing wires and the top layer of reinforcement in Slabs 1 and 2.…”
Section: Long-term Exposure Testsmentioning
confidence: 99%
“…Recent embedded sensors have been used either to determine damaging conditions for corrosion, or to measure degradation response to damaging conditions. Wireless threshold sensors were studied by Dickerson, et al [18], in which a sensing steel wire component in a wireless passive sensor was interrogated with an inductively coupled magnetic monitor to determine the corrosion damage of steel in concrete test structures. Corrosion of the wire disrupted the electrical connection and caused the sensor signal to fail (i.e.…”
Section: Introduction To Wireless Corrosion Sensorsmentioning
confidence: 99%
“…Passive, wireless corrosion sensors have been developed to the early detection of corrosion using non invasive techniques and have been proved effective in monitoring localized defect [1][2][3][4][5] . The passive wireless sensors are embedded in concrete, and interrogated by inductively coupled magnetic fields to determine if a corrosion threshold has been reached.…”
Section: Introductionmentioning
confidence: 99%